Effects of Allium sativum Bulb Extract, Diminazene Aceturate and Their Combination on Parasitaemia, and Biochemical Indices in Rats Experimentally Infected with Trypanosoma Brucei Brucei - Peni IJ, Ajagbonna OP, Elinge CM, Agaie BM, Elsa AT, Yusuf H, Ribah IM (Journal of Applied Pharmaceutical Science)
Thirty five clinically healthy albino rats of both sexes weighing between 100 – 120grams were used to study the effects of Allium sativum bulb extract in combination with diminazene aceturate on parsitemia and biochemical indices in trypanosome brucei brucei infection. The rats were divided in to seven groups (A-G) of five rats each. All the infected rats developed Parasitemia five days post infection. Weakness, increase respiratory rate, rough hair coat Biochemical changes at interval and possible deaths were the major parameters which were carefully observed. All the treatment commenced at the onset of parasitemia by day five post infection. Sub therapeutic dose of Allium sativum at 20mg/kg/bw in combination with 1.7mg/kg/bw of diminazene aceturate (Group C),diminazene aceturate at single standard dose of 3.5mg/kg/bw (Group B) caused a significant reduction (P
Keywords: Allium sativum,Diminazene aceturate,Trypanosoma brucei brucei,Rats,SerumLiver enzymes.